2019
DOI: 10.28991/cej-2019-03091307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glass Fibers on Mechanical Properties of Concrete with Recycled Coarse Aggregates

Abstract: Despite plain cement concrete presenting inferior performance in tension and adverse environmental impacts, it is the most widely used construction material in the world. Consumption of fibers and recycled coarse aggregates (RCA) can add ductility and sustainability to concrete. In this research, two mix series (100%NCA, and 100%RCA) were prepared using four different dosages of GF (0%GF, 0.25%GF, 0.5%GF, and 0.75%GF by volume fraction).  Mechanical properties namely compressive strength, splitting tensile str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…This behavior agrees with that reported in various investigations. Ali et al found in their investigation of glass fibers incorporated in concrete with RCA that when RCA completely replaces NCA, it reduces the compressive strength, split tensile strength and flexure strength by about 12%, 11% and 8%, respectively [ 69 ]. Kurda et al concluded that both materials, FA and RCA, are detrimental to the mechanical properties of concrete.…”
Section: Methodsmentioning
confidence: 99%
“…This behavior agrees with that reported in various investigations. Ali et al found in their investigation of glass fibers incorporated in concrete with RCA that when RCA completely replaces NCA, it reduces the compressive strength, split tensile strength and flexure strength by about 12%, 11% and 8%, respectively [ 69 ]. Kurda et al concluded that both materials, FA and RCA, are detrimental to the mechanical properties of concrete.…”
Section: Methodsmentioning
confidence: 99%
“…The most commonly investigated type of fiber reinforcement in RC is steel fiber with and without mineral admixtures [13,14,17,18]. Polypropylene, basalt, and glass fibers have also been investigated in RC [19][20][21][22][23][24][25][26]. These studies have shown that fibers mainly contribute to flexural and tensile strength of RC.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical performance percentage of plain and fibre concrete mixes was calculated using the equation proposed by Ali et al [40].…”
Section: Resultsmentioning
confidence: 99%